Cardiovascular protective effect of cinnamon and its major bioactive constituents: An update. (October 2022) - Das, Gitishree; Gonçalves, Sandra; Basilio Heredia, J.; Romano, Anabela; Jiménez-Ortega, Luis Alfonso; Gutiérrez-Grijalva, Erick P.; Shin, Han Seung; Patra, Jayanta Kumar
Graphical abstract: Highlights: Cinnamon is the most important spice used worldwide in food (traditional medicine). Substantial benefits for human health, its protective role on cardiovascular diseases. It exhibited beneficial effects on cardiovascular-related comorbidities like diabetes & metabolic syndrome. Cinnamaldehyde and cinnamic acid are main cinnamon compounds with cardiovascular protective effects. Abstract: Cinnamon from the bark of Cinnamomum species is one of the most important spices used worldwide in food and as a traditional medicine for centuries. It has substantial benefits for human health including its protective role on cardiovascular diseases. This review provides an overview of the cardiovascular protective effects of cinnamon and its major bioactive constituents. Reviewed literature showed sufficient evidence that cinnamon can reduce the risk of cardiovascular diseases, including cardiac ischemia, cardiac hypertrophy, and myocardial infarction. Furthermore, cinnamon exhibited beneficial effects on cardiovascular-related comorbidities like diabetes, and other metabolic disorders, and showed antioxidant and anti-inflammatory effects. Cinnamon contains several bioactive compounds such as phenolics and volatile compounds. Cinnamaldehyde and cinnamic acid are among the main cinnamon compounds with protective effects on cardiovascular diseases through different molecular mechanisms. Although the protective effects of cinnamon and its main compounds have been extensively reported, more preclinical and clinical studies are still required before its use as a biopharmaceutical agent.